Student’s entrepreneurial intention: ESCE and FEA comparison - Mares, Pedro (2016)
The decision to become an entrepreneur involves an elaborate mental process. Understand this process during the formation of possible entrepreneurs that means during its educational process is important since entrepreneurship is actually a possible career for an increase number of students. The present study tries to understand the mental process related to students become an entrepreneur following the cognitive approach through the application of Entrepreneurial Intentions Questionnaire (EIQ) to students from College of Business and Administration (ESCE), Polytechnic Institute of Setubal (IPS) and students from Economics and Management College (FEA), University of São Paulo (USP). Consequently the aim of the study is to understand the student’s entrepreneurial intention, considering the influence of social and skills perceptions in determining entrepreneurial intentions. This study allowed the confirmation of the findings of previous studies concerning the relationship between the entrepreneurial intention and the attitudes towards entrepreneurship and perceived behavioural control.